Breaking The Shadows of the Ordinary: A Multiple Case Study On Female Patrol Officers - Mary Abegail B. Orlanda; Ariel A. Alamban (Humanities, Society, and Community, 2026)
Female patrol officers play a crucial role in modern law enforcement, offering unique strengths and perspectives. This study examined the empowerment, resilience, and well-being of female patrol officers and how these factors influence job satisfaction, performance, and safety. Using a qualitative multiple case study design, the research explored the lived experiences of three female patrol officers in Davao del Norte, selected through purposive sampling to represent varying years of service. In-depth, individually conducted interviews were used to gather narrative data, and transcripts were subjected to content and thematic analyses to identify patterns across cases. Findings revealed that ongoing training, skill development, and inclusive decision-making enhance female officers’ effectiveness and support their capacity to manage risks and adapt to complex situations. Participants emphasized strengths such as lower aggression, ethical behavior, empathy, communication skills, and strong community engagement, all of which contribute to improved police–community relations. Results also highlighted the importance of organizational support, leadership opportunities, and inclusive workplace culture in strengthening empowerment and professional growth. The study concludes that investing in the development of female patrol officers fosters a more balanced, capable, and community-responsive police force.